Abnormal Audit Fees and Restatements - Blankley, Alan I.; Hurtt, David N.; MacGregor, Jason E. (Auditing : a journal of practice and theory, 2012)
We investigate the relationship between audit fees and subsequent financial statement restatements in the years following the Sarbanes-Oxley Act of 2002 (SOX). After controlling for internal control quality, we find that abnormal audit fees are negatively associated with the likelihood that financial statements are subsequently restated. This result conflicts with prior work that finds that audit fees are positively associated with future restatements. Overall, our evidence is consistent with the notion that restatements reflect low audit effort or underestimated audit risk in the periods leading up to the restatement year.